Targeting DNA Damage Response in Prostate Cancer by Inhibiting Androgen Receptor-CDC6-ATR-Chk1 Signaling - Karanika, Styliani; Karantanos, Theodoros; Li, Likun; Wang, Jianxiang; Park, Sanghee; Yang, Guang; Zuo, Xuemei; Song, Jian H.; Maity, Sankar N.; Manyam, Ganiraju C.; Broom, Bradley; Aparicio, Ana M.; et al. (Cell reports (Cambridge), 2017)
Cell division cycle 6 (CDC6), an androgen receptor (AR) target gene, is implicated in regulating DNA replication and checkpoint mechanisms. CDC6 expression is increased during prostate cancer (PCa) progression and positively correlates with AR in PCa tissues. AR or CDC6 knockdown, together with AZD7762, a Chk1/2 inhibitor, results in decreased TopBP1-ATR-Chk1 signaling and markedly increased ataxia-telangiectasia-mutated (ATM) phosphorylation, a biomarker of DNA damage, and synergistically increases treatment efficacy. Combination treatment with the AR signaling inhibitor enzalutamide (ENZ) and the Chk1/2 inhibitor AZD7762 demonstrates synergy with regard to inhibition of AR-CDC6-ATR-Chk1 signaling, ATM phosphorylation induction, and apoptosis in VCaP (mutant p53) and LNCaP-C4-2b (wild-type p53) cells. CDC6 overexpression significantly reduced ENZ- and AZD7762-induced apoptosis. Additive or synergistic therapeutic activities are demonstrated in AR-positive animal xenograft models. These findings have important clinical implications, since they introduce a therapeutic strategy for AR-positive, metastatic, castration-resistant PCa, regardless of p53 status, through targeting AR-CDC6-ATR-Chk1 signaling. [Display omitted] •CDC6 expression is increased during prostate cancer (PCa) progression•AR or CDC6 knockdown, together with AZD7762, suppresses TopBP1-ATR-Chk1 signaling•AR or CDC6 knockdown sensitizes PCa cells to AZD7762•Enzalutamide and AZD7762 combination treatment generates synergistic therapeutic effects CDC6 is an androgen receptor (AR) target gene and an essential regulator of DNA replication and checkpoint activation. Karanika et al. show that combined inhibition of the AR and Chk1 signaling promotes DNA damage accumulation in prostate cancer cells to induce cell death, regardless of p53 status.